The Effect Of Work Experience And Work Skills On The Work Productivity Of Members Of The Regional Police Traffic Directorate. Metro Jaya - Arif Fadil; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Digital Business Management, 2026)
The purpose of this study was compiled to answer the formulation of the problem that has been determined, namely analyzing the influence of work experience on the work productivity of members, To analyze the influence of work skills on the work productivity of members To analyze the influence of work experience and work skills simultaneously on the work productivity of members of the Traffic Directorate of Polda Metro Jaya. There is an influence of work experience on the work productivity of members as evidenced by the calculated t value for variable X 1 ( work experience ) of 5.313, while the t table value for n = 65 is 1.997 . So t count > t table or 5.313> 1.997, There is an influence work skills towards The productivity of the members' work is proven by the calculated t value for variable X 2 ( work skills ) of 7.073 , while the t table value for n = 65 is 1.997 . So the calculated t > t table or 7.073 > 1.997. The probability value (significance) = 0.000. So the probability of 0.000 is below 0.05. Thus, H0 is rejected and Ha is accepted. There is an influence Work experience and work skills together have an influence on the variable of work productivity of members, the value of which is proven The calculated F value is 54.112, which is greater than the F table of 2.75 with a significance level of 0.000 because 0.000 < 0.05.